Nationwide Assessment of Population Structure, Stability and Plant Morphology of Two Mimusops Species along a Social-Ecological Gradient in Benin, West Africa - Gisèle K. Sinasson S. (MDPI AG, 2021)
Understanding tree species autecology and population structure supports effective conservation actions. Of particular importance are multipurpose trees that provide non-timber forest products (NTFPs). We assessed the population structures and morphologies of two species of NTFP trees in the genus Mimusops across bioclimatic zones in Benin by sampling 288 plots within 11 forests. Structural characteristics were compared between species, forests and zones. Correlations were also observed between Mimusops tree regeneration density, tree features and ecological characteristics. The density of trees ≥5 cm and of regeneration and mean tree height were higher for M. andongensis (within more protected forest) than M. kummel (in forests with access to people), while the highest mean diameter was observed for M. kummel. Tree and regeneration densities and mean height were greatest in the humid zone of Benin, whilst the largest mean diameter was obtained in the sub-humid zone. The results showed significant correlations between regeneration density and soil properties for M. andongensis but not for M. kummel. The correlations between tree morphology and soil characteristics were weak for both species. Ecological characteristics, along with the species’ functional traits and pressures, are important factors related to the observed differences between the species. All diameter classes were represented, and the population seemed more stable in the more protected forest relative to other forests. Mimusops trees with a diameter of 5–15 cm represented more than 30% of this species in most forests; this suggests, for M. kummel, whose trees flower when quite small (≥6 cm dbh), that there are sufficient reproductive trees. Thus, as a long-lived species, its populations could be maintained even with low/episodic recruitment. However, we found no regeneration in many forests and climate change could threaten populations. Therefore, it is important to investigate regeneration growth and dynamics, seed production and germination of the species in relation to the biophysical conditions and disturbances experienced by Mimusops stands.